2021
DOI: 10.1002/cne.25115
|View full text |Cite
|
Sign up to set email alerts
|

Chronic stress differentially altersmRNAexpression of opioid peptides and receptors in the dorsal hippocampus of female and male rats

Abstract: Chronic immobilization stress (CIS) results in sex‐dependent changes in opioid peptide levels and receptor subcellular distributions within the rat dorsal hippocampus, which are paralleled with an inability for males to acquire conditioned place preference (CPP) to oxycodone. Here, RNAScope in situ hybridization was used to determine the expression of hippocampal opioid peptides and receptors in unstressed (US) and CIS estrus female and male adult (∼2.5 months old ) Sprague Dawley rats. In all groups, dentate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 66 publications
1
10
0
Order By: Relevance
“…(2010)]. The presence of DOR‐immunoreactivity (‐ir) with AB1560 in interneurons and pyramidal cells in the rat hippocampus is consistent with mRNA expression (Johnson et al., 2020; Mansour et al., 1994) and binding (Crain et al., 1986; Gulya et al., 1986; Mansour et al., 1987; McLean et al., 1987) for DOR in this species.…”
Section: Methodssupporting
confidence: 61%
See 2 more Smart Citations
“…(2010)]. The presence of DOR‐immunoreactivity (‐ir) with AB1560 in interneurons and pyramidal cells in the rat hippocampus is consistent with mRNA expression (Johnson et al., 2020; Mansour et al., 1994) and binding (Crain et al., 1986; Gulya et al., 1986; Mansour et al., 1987; McLean et al., 1987) for DOR in this species.…”
Section: Methodssupporting
confidence: 61%
“…Furthermore, no detectable labeling of this antibody is seen in Western blots of COS-7 cells (see Supporting information Figure S1 in Williams et al 2011a), which do not endogenously express DORs (Kieffer et al, 1992) and in the dorsal raphe of DOR knockout mice [see Supporting information Figure S1 in Bie et al (2010)]. The presence of DOR-immunoreactivity (-ir) with AB1560 in interneurons and pyramidal cells in the rat hippocampus is consistent with mRNA expression (Johnson et al, 2020;Mansour et al, 1994) and binding (Crain et al, 1986;Gulya et al, 1986;Mansour et al, 1987;McLean et al, 1987) for DOR in this species.…”
Section: Antibody Characterizationmentioning
confidence: 80%
See 1 more Smart Citation
“…In certain instances, it appeared that Δ 9 -THC exposure significantly affected mRNA expression of opioid-related units during the prenatal period, with these alterations affecting the opioid system long into adulthood. This explanation received recent validation with other paradigms also demonstrating a proclivity of Δ 9 -THC to differentially alter the mRNA expression of opioid peptides and receptors [ 135 ]. Such molecular alterations may reflect the secondary means of dopaminergic activity regulation previously mentioned.…”
Section: Discussionmentioning
confidence: 99%
“…Our sensitivity analysis in sons and daughters indicates that paternal regular use of opioid (inhaling) is associated with higher odds ratio of obesity only in sons (201% increase in final adjusted model), and no significant increase was observed in daughters. The underlying reason for this differential response of male and female offspring to parental opioid inhaling may be a cultural factor that sons are more in company of their fathers at the time of opioid inhaling, or it may be the biologically known sex differences in response to opioids based on the differences in neuroimmune and hormonal systems [29][30][31][32][33][34] . www.nature.com/scientificreports/ On the other hand, we found that paternal opioid use pre-fatherhood is significantly associated lower odds ratio of underweight in offspring.…”
Section: Discussionmentioning
confidence: 99%